Dietary expansion facilitates the persistence of a large frugivore in fragmented tropical forests - Magioli, Marcelo (2021)
How species persist in fragmented habitats is essential to understanding species resilience in response to increasing anthropogenic pressures. It has been suggested that expansion in dietary niche allows populations to persist in human-modified landscapes, yet this hypothesis has been poorly tested in highly diverse ecosystems such as tropical forests where frugivory is ubiquitous. Here, we measured dietary niche expansion of a large forest-dwelling mammal, the white-lipped peccary (Tayassu pecari), in the Atlantic Forest, Brazil, by comparing its diet using stable carbon (δ13C) and nitrogen (δ15N) isotopes. We collected hair of white-lipped peccaries in three continuous and three fragmented forests and compared δ13C and δ15N values, resource use and isotopic niches among populations and between forest types. We also tested the relationship between isotopic values of the populations and the forest cover percentage. White-lipped peccaries fed mainly on forest sources (C3 resources), especially in continuous forests, but 28% of the individuals in fragmented sites also incorporated C4 resources to some extent. In fragmented forests, the populations had isotopic niches from 3- to 3.6-fold the size of those in continuous forests. This niche expansion was due to the consumption of food items with higher δ15N values and C4 crops. Differences among populations were larger among fragmented forests, suggesting variable site-specific strategies to cope with habitat loss. The mean isotopic values of white-lipped peccary populations were negatively correlated with the loss of forest cover. Some small forest fragments might still retain relatively high habitat quality, and white-lipped peccaries might be able to capitalize on such variety of resources, shifting their diets from those observed in continuous forests. We suggest that high dietary flexibility and dietary expansion toward consumption of non-forest resources might facilitate the persistence of large frugivores in fragmented habitats.